Nutrition Intake And Hemoglobin Levels In Pregnant Women - Stephanie, Felicia (Jurusan Gizi Poltekkes Kemenkes Makassar, 2021)
Pregnancy is a physiological-specific period where during pregnancy there is an increased need for nutrients and a bad diet will have a negative impact on nutritional disorders in the body, such as anemia. According to Riskesdas data in 2018, the prevalence of anemia in pregnant women was 48.9%, while in 2013 it was 37.1%. Therefore, it can be concluded that the prevalence of anemia in pregnant women has increased. This study aims to analyze the relationship between nutrient intake (protein, Fe, vitamin B12, and vitamin C) and hemoglobin levels controlled by gestational age in pregnant women. This research is descriptive observational with a quantitative method with cross-sectional approach. This study involved 50 second and third trimester pregnant women who examined the womb at the Kebon Jeruk Regional Health Center by taking the sample through the purposive sampling method. The statistical test used is partial correlation. Data on the characteristics of pregnant women obtained in this study were the average age of pregnant women of 28.64 ± 5.50 years; the mean gestational age was 23.76 ± 8.49 weeks; the average hemoglobin level was 12.19 ± 1.02 g/dL; the average protein intake was 94.75 ± 35.17 grams; the average iron intake was 21.02 ± 15.15 grams; the average intake of vitamin C was 116.83 ± 124.11 milligrams; and the average intake of vitamin B12 was 9.43 ± 8.83 micrograms. The results of this study indicated that there was no significant relationship between nutrient intake (protein, Fe, vitamin B12, and vitamin C) and hemoglobin levels were controlled for gestational age (p> 0.05). Therefore it can be concluded that there is no significant relationship between nutrient intake (protein, Fe, vitamin B12, and vitamin C) and hemoglobin levels in this study.